Cost-driven screening of network constraints for the unit commitment problem - Porras, Álvaro; Pineda-Morente, Salvador; Morales-González, Juan Miguel; Jiménez-Cordero, María Asunción (The Institute of Electrical and Electronics Engineers (IEEE), 2022)
In an attempt to speed up the solution of the unit commitment (UC) problem, both machine-learning and optimization-based methods have been proposed to lighten the full UC formulation by removing as many superfluous line-flow constraints as possible. While the elimination strategies based on machine learning are fast and typically delete more constraints, they may be over-optimistic and result in infeasible UC solutions. For their part, optimization-based methods seek to identify redundant constraints in the full UC formulation by exploring the feasibility region of an LP-relaxation. In doing so, these methods only get rid of line-flow constraints whose removal leaves the feasibility region of the original UC problem unchanged. In this paper, we propose a procedure to substantially increase the line-flow constraints that are filtered out by optimization-based methods without jeopardizing their appealing ability of preserving feasibility. Our approach is based on tightening the LP-relaxation that the optimization-based method uses with a valid inequality related to the objective function of the UC problem and hence, of an economic nature. The result is that the so strengthened optimization-based method identifies not only redundant line-flow constraints but also inactive ones, thus leading to more reduced UC formulations.
Keywords: Circuitos de interfaces; Circuitos lógicos; Ingeniería - Estimación de costes; Optimización combinatoria; Energía - Consumo; Bounding; Constraint screening; Cost-driven approach; Optimization-based method; Unit commitment